Плагіат як сучасне правопорушення - Виноградська, В. Г. (ХНУРЕ, 2023)
Plagiarism has become an increasingly pervasive issue in today's world, particularly with the widespread use of digital technology and the internet. Ukraine is no exception, and the country has implemented specific legislation to combat plagiarism and protect intellectual property. This article will discuss the legal framework for plagiarism in Ukraine, including the penalties for copyright infringement and the professional and academic repercussions of committing plagiarism. Additionally, the article will provide recommendations for individuals to avoid plagiarism, such as proper citation and the use of plagiarism detection software.